Rapid analysis of CpG methylation patterns using RNase T1 cleavage and MALDI-TOF - Schatz, Philipp (Oxford University Press, 2004)
Here, we introduce a method for the fast and accurate analysis of DNA methylation based on bisulfite-treated DNA. The target region is PCR amplified using a T7 RNA polymerase promoter-tagged primer. A subsequent in vitro transcription leads to a transcript which contains guanosine residues only at sites that contained methylated cytosines before bisulfite treatment. In a single tube reaction using guanosine-specific cleavage by RNase T1, a specific pattern of RNA fragments is formed. This pattern directly represents the methylation state of the sample DNA and is analyzed using matrix-assisted laser desorption ionization time-of-flight technology. This method was successfully applied to the analysis of artificially methylated and unmethylated DNA, mixtures thereof and colon DNA samples. The applicability for the analysis of both PCR products and cloned PCR products is demonstrated. The observed methylation patterns were confirmed by bisulfite sequencing.